2014
DOI: 10.5194/tcd-8-5961-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climatic signals from 76 shallow firn cores in Dronning Maud Land, East Antarctica

Abstract: Abstract. The spatial and temporal distribution of surface mass balance (SMB) and δ18O were investigated in the first comprehensive study of a set of 76 firn cores retrieved by various expeditions during the past three decades in Dronning Maud Land, East Antarctica. The large number of cores was used to calculate stacked records of SMB and δ18O, which considerably increased the signal-to-noise ratio compared to earlier studies and facilitated the detection of climatic signals. Considerable differences between … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…Still, on the East Antarctic Plateau, a clear seasonal cycle is depicted in the isotopic composition of the precipitation (Fujita and Abe, 2006;Landais et al, 2012;Stenni et al, 2016) and of the surface snow (Touzeau et al, 2016). So far, whether this seasonal cycle is archived or not in buried snow, and thus, whether stacking an array of snow pits enables us to increase the signal to 20 noise ratio and depict a climatic record at the seasonal scale from water isotopic signal is an important open question (Ekaykin et al, 2014;Altnau et al, 2015;Münch et al, 2016Münch et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Still, on the East Antarctic Plateau, a clear seasonal cycle is depicted in the isotopic composition of the precipitation (Fujita and Abe, 2006;Landais et al, 2012;Stenni et al, 2016) and of the surface snow (Touzeau et al, 2016). So far, whether this seasonal cycle is archived or not in buried snow, and thus, whether stacking an array of snow pits enables us to increase the signal to 20 noise ratio and depict a climatic record at the seasonal scale from water isotopic signal is an important open question (Ekaykin et al, 2014;Altnau et al, 2015;Münch et al, 2016Münch et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Present available observation dataset, however, is of insufficient length to address that these warming trends are anthropogenically forced, because natural interannual to multi-decadal variability may obscure these warming trends (Jones et al 2016). While no significant warming trends have been recorded in East Antarctica (EA) in recent decades (Altnau et al 2014), surface snowmelt is observed every summer over ice shelves, even in the East Antarctic coast (Toriensi et al 2003;Picard and Fily 2006;Trusel et al 2013). Even a slight increase in the summer air temperature on the East Antarctic coast therefore is expected to enhance surface melt and its role in ice loss.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (Altnau et al, 2015;Vega et al, 2016; report negative SMB trends in coastal areas contrary to positive trends for the plateau. For our study period (17 years for the TA record, 16 years 5 for the ECHAM5-wiso simulation), a slightly increasing but not significant trend (Agosta et al, 2012), the TA firn core, the ERA or ECHAM5-wiso data.…”
Section: Smbmentioning
confidence: 96%